Socialization of the Importance of Saving from an Early Age to Elementary School Students in Bongas Village, Indramayu Regency - Anisa Dewi (Annujum: Journal of Humaniora and Law, 2025)
Saving is the activity of setting aside some of the money or income you have for savings with the aim of managing that money. The benefits of saving can be obtained when we carry out this saving activity regularly and diligently. This aims to lead a frugal lifestyle and is also a characteristic development of not wasting money which should be implemented from an early age. In this community service activity, there was a socialization about "The importance of saving from an early age" to students in Bongas Village, considering that there is still a low culture of saving among children, especially saving at a bank. This activity aims to provide students with an understanding of the importance of saving and its benefits for the future, motivate students to want to save so as to raise awareness among students to be able to set aside a small portion of their pocket money for savings. Also to improve the economy to prevent the spread of stunting because one of the causes of stunting can also be due to economic deficiencies. The method for implementing this coomunity service is through socialization and interactive counseling methods offline or face to face while still paying attention to health protocols. The community service team came to the school and then provided information to students by delivering material about the importance of saving from an early age, then a question and answer quiz was held and students who could answer the questions received prizes in the form of piggy banks. The results achieved from the program to socialize the importance of saving from an early age were that this event was held once during community service, namely on July 29 2022. This activity was carried out at SDN 1 Bongas. The number of students who took part in this activity was 27 people. They are the total number of grade 5 students at SDN 1 Bongas. They were taught what saving was and were immediately given piggy banks as a gift so they could immediately practice saving in their respective homes. They looked enthusiastic and gave a positive response to the importance of saving at an early age. So that students understand the importance of saving from an early age by being more thrifty and being able to spend the pocket money they get from their parents wisely. The follow-up to this activity is that the role of parents is needed to control and re-emphasize the understanding of the importance of saving in order to hone their children's mentality so they can save money.